Jet Ventilation in the Pregnant Patient with Airway Stenosis: Surgical Safety and Outcomes. (May 2020) - Heichel, Philip D.; Jacobsen, Christian P.; Llamas, Luis L.; Simpson, C. Blake; Lott, David G.; Verma, Sunil; Dominguez, Laura M.
Objective: To review pregnancy outcomes and the safety of jet ventilation use in the gravid patient undergoing surgical airway intervention. Methods: A multi-institutional retrospective review of medical records was performed to identify women who underwent low-frequency jet ventilation during pregnancy for surgical treatment of airway stenosis. Postoperative complications were noted, and patients were interviewed regarding pregnancy outcomes. Results: Six women were included in this series. No immediate complications relating to anesthesia or surgical intervention were noted in five of the six women. One patient with a well-known history of uncontrolled seizures experienced seizure activity postoperatively. One patient returned to the operating room at a later date for debridement of tracheal crusts. Five mothers delivered via cesarean section and one via spontaneous vaginal delivery. The mean gestation age was 37.3 weeks. One of the six infants delivered prematurely and three were delivered at low birth weight. Three of the six infants required elevated care immediately post-delivery but, at present, all are in good health. Conclusion: Low-frequency jet ventilation and surgical management of airway stenosis should be recognized as a safe treatment option in the gravid patient. Surgical intervention should not be delayed in patients with severe symptoms, particularly given the potential risk associated with prolonged corticosteroid use. Level of evidence: 4